Intermittent fasting promotes prolonged associative interactions during synaptic tagging/capture by altering the metaplastic properties of the CA1 hippocampal neurons - Dasgupta, Ananya; Kim, Joonki; Manakkadan, Anoop; Arumugam, Thiruma, V; Sajikumar, Sreedharan (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2018)
Metaplasticity is the inherent property of a neuron or neuronal population to undergo activity-dependent changes in neural function that modulate subsequent synaptic plasticity. Here we studied the effect of intermittent fasting (IF) in governing the interactions of associative plasticity mechanisms in the pyramidal neurons of rat hippocampal area CA1. Late long-term potentiation and its associative mechanisms such as synaptic tagging and capture at an interval of 120 min were evaluated in four groups of animals, AL (Ad libitum), IF12 (daily IF for 12 h), IF16 (daily IF for 16 h) and EOD (every other day IF for 24 h). IF had no visible effect on the early or late plasticity but it manifested a critical role in prolonging the associative interactions between weak and strong synapses at an interval of 120 min in IF16 and EOD animals. However, both IF12 and AL did not show associativity at 120 min. Plasticity genes such as Bdnf and Prkcz, which are well known for their expressions in late plasticity and synaptic tagging and capture, were significantly upregulated in IF16 and EOD in comparison to AL. Specific inhibition of brain derived neurotropic factor (BDNF) prevented the prolonged associativity expressed in EOD. Thus, daily IF for 16 h or more can be considered to enhance the metaplastic properties of synapses by improving their associative interactions that might translate into an improved memory formation.